Characteristics of Thyroid Neoplasm Patients in the Department of Anatomic Pathology, Aloei Saboe Hospital - Trinny Tuna; Nur Hijra Puji Astuti; Sri Andriani Ibrahim; Abdi Dzul Ikram Hasanuddin; Romy Abdul (Universitas Negeri Gorontalo, 2023)
Introduction: Thyroid Neoplasm is a tumor originating from the thyroid gland. Thyroid neoplasms encompass both benign and malignant tumors. Thyroid malignancies are among the most frequently encountered malignancies of the endocrine glands. Thyroid neoplasms generally have a relatively good prognosis when detected early. This study aims to determine the characteristics of thyroid neoplasm patients in the Department of Anatomic Pathology, Aloei Saboe Hospital.Method: This study is descriptive research using secondary data from medical records. Data was collected using a total sampling technique with a sample size of 58 patients. The study was conducted in the Department of Anatomic Pathology, Aloei Saboe Hospital, from January 2021 to October 2022.Results: The distribution of thyroid neoplasm patients is highest in late adulthood (36-45 years) with 15 patients (25.9%), followed by early elderly (46-55 years) with 15 patients (25.9%). The gender distribution shows more female patients, accounting for 43 (77.6%). The most common histopathological type is Colloid Goiter, with 20 patients (34.5%).Conclusion: The distribution of thyroid neoplasm patients is most prevalent between the ages of 35 to 55 years, predominantly in females, with the most common histopathological finding being Colloid Goiter. This study is expected to serve as a valuable source of information, enhancing public knowledge and awareness regarding thyroid neoplasm patients' characteristics.